Energia fotovoltaica: análise técnica e econômica de sistema autônomo para irrigação - Bruning, Jhosefe (2022)
The use of renewable energy sources has been seen as an alternative to reduce environmental impacts. Associated with this, climate change and dependence on fossil fuels strengthen photovoltaic energy generation, which has increasing expansion in the energy sector as a sustainable source. Brazil has high potential for the use of photovoltaic energy, including within agricultural production systems. What makes it possible solar water pumping an attractive option for irrigation in view of rising fuel costs and electricity shortages in many regions. Therefore, the present study objective to analyze the technical and economic feasibility of "offgrid" photovoltaic energy systems to drive pumping systems for irrigation. The study was developed through the simulations of photovoltaic systems in autonomous operation, without the use of batteries and without other energy sources, being suitable for supplying energy in order to meet different driving powers of water pumping systems for small sprinkler irrigation, with powers of up to 29.4 kW during the day. To the photovoltaic projects, data was collected regarding the availability of solar resources for energy generation. Thus, different off-grid photovoltaic energy systems were dimensioned, to meet the different driving powers, in order to supply the necessary volume of water during the sunny hours. Subsequently, the economic feasibility analysis was carried out through the calculation of the main economic indices with net present value, internal rate of return, benefit/cost ratio, profitability index and sensitivity analysis. With that, it was found that the irrigation with a solar energy system is a viable alternative, where stand-alone photovoltaic systems without energy storage are technically viable to serve systems with powers up to 15 hp. In addition to an economically viable alternative. The photovoltaic power generation projects presented increasing costs in relation to the increase in power and the cost normalized by the power presents economy of scale. In relation to the powers used, the levelized cost of energy (LCOE) demonstrated feasibility. The sensitivity analysis returned profitability in relation to price variation product and deployment costs. Therefore, the use of solar energy systems for irrigation in areas with available and levels of radiation is a viable alternative, increasing the sustainability and profitability of irrigated agriculture